2010
DOI: 10.1099/mic.0.036723-0
|View full text |Cite
|
Sign up to set email alerts
|

A sulphite-inducible form of the sulphite efflux gene SSU1 in a Saccharomyces cerevisiae wine yeast

Abstract: Sulphite is widely used as a preservative in foods and beverages for its antimicrobial and antioxidant activities, particularly in winemaking where SO 2 is frequently added. Thus, sulphite resistance mechanisms have been extensively studied in the fermenting yeast Saccharomyces cerevisiae. Sulphite detoxification, involving a plasma membrane protein encoded by the SSU1 gene, is the most efficient resistance mechanism in S. cerevisiae. In this study, we characterized the unusual expression pattern of SSU1 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 31 publications
2
55
0
4
Order By: Relevance
“…The kanamycin ⍀ cassette replacing Alvin_3072 therefore most likely also prevents formation of the Alvin_3073-encoded transporter, and more experiments are needed to exactly dissect the effect exerted by the interposon. The protein Alvin_3073 belongs to a family of transporters that includes a malate uptake system in the yeast Schizosaccharomyces pombe (63), a tellurite resistance protein in Escherichia coli (64), and notably, a sulfite efflux pump in Saccharomyces cerevisiae and other fungi, including Aspergillus fumigatus (65). Alvin_3072 is conserved in several sulfide-oxidizing bacteria (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The kanamycin ⍀ cassette replacing Alvin_3072 therefore most likely also prevents formation of the Alvin_3073-encoded transporter, and more experiments are needed to exactly dissect the effect exerted by the interposon. The protein Alvin_3073 belongs to a family of transporters that includes a malate uptake system in the yeast Schizosaccharomyces pombe (63), a tellurite resistance protein in Escherichia coli (64), and notably, a sulfite efflux pump in Saccharomyces cerevisiae and other fungi, including Aspergillus fumigatus (65). Alvin_3072 is conserved in several sulfide-oxidizing bacteria (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other described sulfite efflux pumps stem from fungal sources, e.g. SSU1 from Saccharomyces cerevisiae (Park & Bakalinsky, 2000;Nardi et al, 2010) or Aspergillus fumigatus (Léchenne et al, 2007). However, genes encoding closely related proteins are not present in the currently sequenced purple sulfur bacteria with the exception of Thiorhodococcus drewsii.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Kloeckera apiculata and Hansenula anomala were shown to be highly sensitive to SO 2 (Warth 1985). Strains of S. cerevisiae have been shown to be fairly tolerant to SO 2 in general when compared with other yeast species but display highly diverse SO 2 tolerance (Divol et al 2006;Nardi et al 2010). It was reported that in a spontaneous wine fermentation, 50 mg/L SO 2 in general is sufficient to inhibit most of the non-Saccharomyces yeasts found in grape juice except Candida spp.…”
Section: Resistance To So 2 In Wine Yeastsmentioning
confidence: 96%
“…However, there is an absence of heterozygosity for the untranslocated locus (i.e. on chromosome VIII) (Aa et al 2006;Liti et al 2009;Nardi et al 2010). As wine strains of S. cerevisiae exhibit different degrees of ploidy and different levels of heterozygosity, the number of SSU1 and SSU1-R could potentially explain the diverse range of resistance observed between strains.…”
Section: Intracellular Accumulation and Active Effluxmentioning
confidence: 97%
See 1 more Smart Citation